Quality Management Applied to Higher Education Institutions (Research, Society and Development, 2018)
Brazil is experiencing serious economic difficulties in an unstable and complex scenario. There is a great transformation of the market and organizations worldwide, but many companies or institutions often do not follow the transformations, and this adaptability of organizations is one of the greatest factors of success and perennially. Being attentive to market transformations does not only mean following the technology and the new products developed, but rather being in direct and constant contact with all stakeholders of the organization, understanding the changing needs, behaviors, technology and business models, gradually seeking to deliver more value and a better experience for its customers. This analysis becomes even more complicated when dealing with the public sector, as bureaucratic processes and availability of funds lead to great difficulties in the development of these organizations. This course completion project aims to define a procedure for applying quality management in a simple and didactic way in higher education institutions, followed by a case study applied in the production engineering course of the Federal University of Espírito Santo, which identified improvement points and started the validation process of the proposals. Finally, it is expected that such work will help in improving the educational environment for greater efficiency in the training of professionals.